Pendidikan Karakter dalam Bingkai Pancasila: Studi Kritis Pendidikan dalam Perspektif Pedagogik - Minarti Sulistia Ningsih; Yusuf Tri Herlambang; Tatang Muhtar (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The values of Pancasila are increasingly fading due to numerous disparities stemming from a lack of societal awareness to practice Pancasila values in daily life. Moreover, data indicates that Indonesian society is significantly detached from the ideals of Indonesian humanity, which highly regards Pancasila as a philosophy of state life. The purpose of this research is to theoretically analyze and critically study character education that can strengthen Pancasila values among the Indonesian people from a pedagogical perspective. By utilizing the literature study method (library research), data is collected to understand and examine theories from various literatures related to the critically reviewed research title. The research findings indicate a correlation between character education oriented towards Pancasila and pedagogy, where their close relationship aligns with the ultimate goals of Indonesia's national education. These goals include developing individuals according to their potential, understanding the essence of humanity and education, and becoming beings of existence and multidimensionality who are capable of implementing the noble values of Pancasila.